PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA KERJA TERHADAP KINERJA KARYAWAN DI PT DUTA HITA JAYA - Salza Rio Pratama; Matdio Siahaan; Haryudi Anas (SINERGI : Jurnal Riset Ilmiah, 2026)
This study aims to analyze the influence of leadership style and work culture on employee performance at PT Duta Hita Jaya. This study employed a descriptive quantitative approach, with data collection using questionnaires distributed to 112 respondents. Purposive sampling was used to determine the sample, and the collected data were analyzed using the statistical tool Smart Partial Least Square (SmartPLS) 4.0. The results showed that leadership style has a positive and significant influence on employee performance, with a R-value of 0.824 and a T-statistic of 12.206. An effective leadership style can increase enthusiasm, initiative, and productivity in completing work. Meanwhile, work culture demonstrated a positive but insignificant influence on performance, with a R-value of 0.137 and a T-statistic of 1.885. Simultaneously, the two variables explained 88.2% of the variation in employee performance (R-Square 0.882). These findings underscore the importance of leadership style in organizations in improving the overall quality of employee work.